2009
DOI: 10.1007/s11104-009-0218-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity of the coarse root system of Prosopis flexuosa, a phreatophyte tree, in the Monte Desert (Argentina)

Abstract: Prosopis flexuosa trees in the Monte Desert grow in dune and inter-dune valleys, where the water table is located at 6-14 m depth. We asked whether trees in the dunes, which are less likely to access the water table, present a coarse surface root architecture that might favor the exploration / exploitation of dune resources, compensating for water table inaccessibility. We characterized the architecture of surface roots of valley and dune trees, together with the soil environment. The dune held 50 % less and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 54 publications
3
44
0
1
Order By: Relevance
“…This confirms that P. flexuosa behaves as a facultative phreatophyte at the mostly arid end of its distribution, with the capacity to access groundwater and to survive entirely on rainfall, as suggested by previous xylem water isotopic analyses (Jobbágy et al 2010). We have previously demonstrated that P. flexuosa trees extend their surface roots deeper into the ground in the dune than in the valley which, coupled with a higher frequency of primary branches, would allow them to access subsurface rainfall-derived water reservoirs in the dune and thus compensate for inaccessibility of the water table (Guevara et al 2010), as occurs in Banksia attenuata dune (b) Photographs of leaves taken from the northern side of the tree crown at different hours; note that the sun is tilted toward the north in the southern hemisphere communities in western Australia (Zencich et al 2002). However, lower leaf W wPD in dune trees than in valley trees in dry periods indicates that plasticity of the former trees' surface roots is insufficient to avoid drought.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This confirms that P. flexuosa behaves as a facultative phreatophyte at the mostly arid end of its distribution, with the capacity to access groundwater and to survive entirely on rainfall, as suggested by previous xylem water isotopic analyses (Jobbágy et al 2010). We have previously demonstrated that P. flexuosa trees extend their surface roots deeper into the ground in the dune than in the valley which, coupled with a higher frequency of primary branches, would allow them to access subsurface rainfall-derived water reservoirs in the dune and thus compensate for inaccessibility of the water table (Guevara et al 2010), as occurs in Banksia attenuata dune (b) Photographs of leaves taken from the northern side of the tree crown at different hours; note that the sun is tilted toward the north in the southern hemisphere communities in western Australia (Zencich et al 2002). However, lower leaf W wPD in dune trees than in valley trees in dry periods indicates that plasticity of the former trees' surface roots is insufficient to avoid drought.…”
Section: Discussionsupporting
confidence: 53%
“…The depth of the water table was 7.1 m below the valley surface (assessed by a hand-dug well) with 25% w/w water in the 1.5-m wide capillary fringe (Jobbágy et al 2010). The dune held *3% w/w rainwater in 1-4 m deep water reservoirs, and both landscape units had a homogeneous sandy soil profile in the root zone (Jobbágy et al 2010;Guevara et al 2010).We studied three populations of P. flexuosa trees that due to their topographical position (valley-dune) or size (adultsapling) could have variable access to the water table and thus, varying dependence on rainfall: adult trees in the valley and the dune, for which we had isotopic evidence indicating different access to the water table (Jobbágy et al 2010), and saplings in the valley [nonreproductive tree-type individuals, base diameter 1.5-4.5 cm (Table 1), 4-10 years old], for which we have no isotopic data with which to distinguish water sources. We selected five similar-sized adult individuals at each landscape unit, and four saplings in the valley (14 individuals in total; Table 1).…”
Section: Experimental Designmentioning
confidence: 99%
“…This fact suggests that the effect of pruning would be even more evident in years when water availability is higher. The response found in small trees, alternatively, might be related to the root architecture of P. flexuosa, which presents a structure modulated by the geomorphology, nutrient availability and water supply (Guevara et al, 2010). P. flexuosa has a deep root system that allows trees to access the water table, thereby regulating the water supply; this provides some relative independence from the sporadic precipitation pulses that are typical in these arid regions (Noy Meir, 1973;Jobbágy et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…All these factors create favorable conditions for Prosopis proliferation. [11,16,22,23], summarizing the competitive advantages of Prosopis in seed production, root system, leaf and pod palatability. Figure 1.…”
Section: Initial Locationmentioning
confidence: 99%